Type 47B Destroyer Drenthe - MULDER, JANTINUS (LANASTA, 2020)
To counter a growing threat of Soviet submarines and aircraft shortly after WWII, the Royal Netherlands Navy ordered new ships. Classified as ASW destroyer (onderzeebootjager), but so close to contemporary destroyers in terms of specifications. Still suffering from the havoc of war the national industry managed to design and construct these ships in two classes. Drenthe was of the more capable Type 47B series.
Keywords: Destroyers (Warships) -- Netherlands.; Destroyers -- Pays-Bas.; oorlogsschepen.